Metformin therapy and severity and mortality of SARS-CoV-2 infection: a meta-analysis - Romero-Ortuno, Roman (My University, 2021)
Background: It has been postulated that metformin could have anti-SARS-CoV-2 action. This raises the hypothesis that people who take metformin may have lower SARS-CoV-2 severity and/or mortality. Objective To conduct a meta-analysis of the association between the use of Metformin and risk of severity and mortality in SARS-CoV-2 infection. Data Sources We searched PubMed, EMBASE, Google scholar, the Cochrane Database of Systematic Reviews and preprint servers (medRxiv and Research Square) for studies published between December 2019 and January 2021. Data was extracted on study location, year of publication, design, number of participants, sex, age at baseline, body mass index, and exposure and outcome definition. Effect statistics were pooled using random effects models with 95% confidence intervals (CI). The quality of included studies was assessed with the Newcastle–Ottawa Scale (NOS). Results Thirty-two observational studies were included, combining to a total sample of 44306 participants. The mean NOS score of included studies was 7.9. Results suggested that metformin use was associated with a reduced risk of SARS-CoV-2 mortality (OR= 0.56, 95% CI: 0.46-0.68, p<0.001; 22 studies) but not to disease severity (OR=0.85, 95% CI: 0.71-1.02, p=0.077; 15 studies). In the subgroup analysis, metformin reduces the risk of mortality (OR = 0.69, 95% CI: 0.55-0.88; p=0.002) and severity (OR = 0.83, 95% CI: 0.70-0.97, p=0.023) in patients aged 70 and above. Conclusions The use of metformin was associated to lower risk of mortality from SARS-CoV-2 infection. This association does not imply causation and further research is required to clarify potential mechanisms.
PUBLISHED
Keywords: SARS-CoV-2 infection; COVID-19; Metformin; Mortality; Type 2 diabetes; Ageing; Immunology, Inflammation & Infection; Age-related disability; Chronic Health Condition; Third age/ageing